(untitled) (Economics and region, 2022)
The essence of human social security as a priority component of national, in particular economic security, is revealed. It has been determined that in the context of the aggravation of the current socio-economic crisis, and the threats associated with COVID-19, the solution of social problems becomes even more important and relevant. A hybrid war poses a particular threat in Ukraine, which significantly affected the state of Ukraine’s national security, in particular, human social security. Its negative consequences are both direct and indirect, which is a real social threat. The impact of a hybrid war on human social security requires the justification of new, more effective mechanisms and tools for its strengthening. It is noted that the analysis and assessment of the state of social security should be systematic, comprehensive, evaluating the following components: the state of well-being and living standards; stability of social relations and organizational structure; level of culture of the society; availability of conditions for the prevention and resolution of social conflicts; processes of desocialization of society, etc. It is emphasized that social security must be considered in the context of a multi-level system, in particular, it must be considered from the point of view of the economic level, namely: nano-, micro-, meso-, macro- and mega-levels. The author’s multi-level system of social security is proposed, which includes five levels: human social security (nano-level); social security of a business entity (micro level); social security of the region (meso level); social security of the state (macrolevel); global social security (mega level). The author’s definitions of the content (essence) of each level of social security and their functional components are given.